Adaptive yet Vulnerable: Supply Chain Models of Ready-to-Wear Clothing Traders in Bandung’s Traditional Markets - Arifianti, Ria; Fordian, Dian; Pamungkas, Mochammad Rifky (Technium Social Sciences Journal, 2026)
Traditional markets remain a vital component of Indonesia’s local economy, particularly in the distribution of ready-to-wear clothing products. However, empirical studies examining supply chain models within traditional market contexts remain limited. This study aims to analyze and model the supply chain structure of ready-to-wear clothing traders in traditional markets in Bandung City. A qualitative descriptive research design was employed, with primary data collected through in-depth interviews, field observations, and supporting literature review. Data were analyzed using descriptive-interpretative techniques, including data reduction, coding, categorization, and triangulation. The findings reveal that the supply chain structure is relatively short and simple, involving producers (garment and small-scale sewing workshops), retailers (kiosk and street vendors), and end consumers. Despite its flexibility, the supply chain relies heavily on informal coordination, social networks, and adaptive procurement strategies, which increases vulnerability to supply fluctuations and price instability. Differences in access to suppliers and inventory strategies between kiosk traders and street vendors further shape supply chain performance. This study concludes that the effectiveness of supply chain management in traditional markets cannot be assessed using modern retail standards alone. Instead, a contextual and adaptive supply chain model is required to strengthen efficiency and sustainability while preserving the inherent flexibility of traditional market systems.